Estudo da fibra de coco como reforço em tijolo de solocimento - Nascimento, Cláudio Mário (2011)
To take care of to the demand of the new constructions in the low income communities and to develop the production of a strengthened alternative brick with staple fibers of coconut, capable to contribute mainly with the recycling of the green and mature coconut in the urban and agricultural lexes, this research was developed, to confection bricks of soil-cement with coconut fiber. Ecologically correct material and of low cost, since the greenhouse use of or oven for burning will be manufactured without. The study it presents a set of tables and graphs that prove good indices found in the values of the density, water absorption, axial compressive strength and isolation term acoustics, with evidential results that make possible the production in industrial character with press mechanics or the place of the workmanship with manual form. The preparation of coconut staple fibers was made of natural form without use of chemical products not to deprive of characteristics the properties mechanical physicist-chemistries and of the same ones. The sixty bricks produced in simple and manual press had been carried through in four lots of fifteen units. The mixture of aggregates was made in four different traces composites for: ground erinaceous, cement, fiber of dry coconut and water; the bricks had been compact in the press and cured in natural way under an area covered during the minimum time of seven days